Evaluation of ATLHAMC12 subchannel code for total loss of flow scenario - Tomáš Křeček; Štěpán Foral (Acta Polytechnica CTU Proceedings)
The ALTHAMC12 subchannel code is a new subchannel code developed by the ALVEL company. The code is intended for DNBR safety analyses of the Czech nuclear power plants. In order to validate the code, a code to code comparison with THALES and VIPRE-01 is provided in this work. The reactor core model was developed and set of initial and boundary conditions has been adopted from a reference study. The comparison is done for steady state nominal parameters and Total Loss of Flow (TLOF) type of accident. The results show that ALTHAMC12 provides a good agreement with the reference codes in the terms of MDNBR value and its positions in the reactor core.